Validation of the schema mode concept in personality disordered offenders. (14th July 2017) - Keulen‐de Vos, Marije; Bernstein, David P.; Clark, Lee Anna; de Vogel, Vivienne; Bogaerts, Stefan; Slaats, Mariëtte; Arntz, Arnoud
Abstract : Purpose: A core element of Schema Therapy (ST) is 'schema modes' or fluctuating emotional states. ST assumes that particular personality pathology consists of specific combinations of maladaptive schema modes. There is confirmatory evidence for the modes hypothesized to be central to borderline and narcissistic personality disorder (PD) in non‐forensic patients. In this study, we tested three aspects of the construct validity of schema modes in cluster‐B personality disordered offenders, examining its factorial validity, and the relations among personality disorders and violence risk. Method: Our sample consisted of 70 offenders who were diagnosed with an antisocial, borderline, or narcissistic PD. Schema modes were assessed with the Schema Mode Inventory (SMI), personality disorders with the Schedule for Nonadaptive and Adaptive Personality‐Forensic Version (SNAP‐FV), and violence risk with the Historical, Clinical, and Risk management scheme (HCR‐20 V2 ). Results: When controlling for the two other PDs, three schema mode factors distinguished antisocial PD as a disorder involving both low scores on internalizing and high scores on externalizing modes, and borderline PD as involving high scores on internalizing modes. Furthermore, the externalizing schema modes were a significant predictor for violence risk inside the hospital. Conclusions: The hypothesized mode models were partially supported for all three PDs. The findings thus provide some support for the construct validity of schema modes in a forensic sample.